Taxonomic review of the genus Argyrops (Perciformes; Sparidae) with three new species from the Indo-West Pacific - Iwatsuki, Yukio; Heemstra, Phillip C. (Zootaxa, 2018)
The Indo-West Pacific sparid genus Argyrops is reviewed, with four valid species and three new species: A. bleekeri Oshi-ma, 1927, A. filamentosus (Valenciennes, 1830), A. megalommatus (Klunzinger, 1870), A. spinifer (Forsskål, 1775), A. caeruleops n. sp., A. flavops n. sp. and A. notialis n. sp. The above seven species can be differentiated on meristic values, ontogenetic and morphological characters, and coloration. Argyrops bleekeri from the western Pacific and A. notialis n. sp. from Western Australia both have only one rudimentary dorsal-fin spine on the first dorsal pterygiophore (which defines the Argyrops bleekeri complex), while the five other congeners have two rudimentary dorsal-fin spines, both associated with the first dorsal pterygiophore. Argyrops filamentosus, A. megalommatus, and A. caeruleops n. sp. have the 3rd dorsal-fin spine filamentous and longest, the defining character of the A. filamentosus complex. Argyrops spinifer (from the Indian Ocean) and A. flavops n. sp. (from the Middle East to Pakistan, but not the Red Sea and probably rare in the Persian Gulf) differ from other complexes in having 4–6 elongated or filamentous dorsal-fin spines (usually 3rd–6th [four spines] or 3rd–8th [six spines]) in juveniles and subadults, with the first 2 dorsal-fin spines rudimentary, the characteristic of the A. spinifer complex. The above three complexes include the seven Argyrops species that are defined and supported by morphological and color differences, genetic distinctions (partial cytochrome b genes, 1,116 bp), and distribution. The nominal species are discussed, together with several geographic variations of A. spinifer from the Indian Ocean, and a key to the species is provided.